An Investigation On The Mechanical And Tribological Properties Of Alloy A356 On The Addition Of WC. (2018) - Krishna, Ajay Ram; Arun, A.; Unnikrishnan, D.; Shankar, Karthik V.
Abstract: Aluminium alloys have broad applications in aerospace and automotive industries due to its high strength to weight ratio. But it is found that aluminium and its alloys are having poor tribological properties, hence its applications are getting limited. Studies reveal that the additions of reinforcements will enhance the mechanical and tribological properties. In this work an investigation was carried out to understand the mechanical and tribological properties of Aluminium matrix composites. Varying weight percentage (1-5%) of tungsten carbide particulates were added to aluminium A356 alloy using stir casting technique. Different compositions of these aluminium matrix composites were cast. The tungsten carbide particulate distribution in the cast was observed using energy dispersive spectroscopy. Various Experiments were carried out to study the Mechanical and Tribological properties of these Aluminium matrix composites. The results of this investigation reveal that the mechanical properties like hardness, tensile strength and tribological properties like wear resistance have improved up to 4 weight percentage of tungsten carbide. It was also found that varying weight percentage of tungsten carbide has no influence on the coefficient of friction.